Language Ideologies in Irish Secondary Schools: A raciolinguistic approach - Stephen Lucek (Teanga: The Journal of the Irish Association for Applied Linguistics)
Educators are in a unique position when it comes to enforcing language ideologies. On the one hand, they are tasked with preparing young people for the world that they will encounter after graduation. On the other hand, they have a duty of care to their students’ well-being. Exploring the language ideologies of educators has proven to be insightful in understanding how raciolinguistic ideologies are prevalent in education. These studies are predicated on a deficit model of disadvantage that is held by some educators. The current paper takes a look at sociolinguistic diversity in Dublin secondary schools, how secondary school principals deal with social class differences in speech and how principals’ ideologies contribute to, and are shaped by, these experiences. Drawing from professional practice interviews with six principals, I will categorise the principals’ attitudes to linguistic diversity through the everyday sociolinguistic practice in their schools using a language ideology perspective. What we find are principals using Standard Language Ideology and/or a deficit model of disadvantage. When viewed through a raciolinguistic lens, this creates a social-class based construction of whiteness and non-whiteness. The principals’ attitudes do not only apply to their students, but extend to teachers in the school as well as society at large. The paper concludes with considerations for how to address socially diverse students in schools, which currently lies outside the official guidance for principals from the National Council for Curriculum and Assessment (NCCA).